THE PROPERNESS OF ADOBE FLASH BASIS INTERACTIVE MEDIA FOR RESPIRATORY SYSTEM LEARNING MATERIAL - Nurbaiti, Nurbaiti; Panjaitan, Ruqiah Ganda Putri; Titin, Titin (Unnes Science Education Journal, 2017)
This study aimed to determine the feasibility of adobe flash-based interactive media on the material of respiratory system. This research was a descriptive qualitative. The data were validated by using questionnaire. The validation was done by three validators. The aspects of validity were software engineering, instructional design, and visual communication. The average score of validity was 3.28 and it was categorized valid. It is concluded that adobe flash-based interactive media is feasible to be used as a learning media on the material of respiratory system.